2017
DOI: 10.1261/rna.064352.117
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the RNA landscape of endothelial exosomes

Abstract: Exosomes are small extracellular vesicles of around 100 nm of diameter produced by most cell types. These vesicles carry nucleic acids, proteins, lipids, and other biomolecules and function as carriers of biological information in processes of extracellular communication. The content of exosomes is regulated by the external and internal microenvironment of the parent cell, but the intrinsic mechanisms of loading of molecules into exosomes are still not completely elucidated. In this study, by the use of next-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 89 publications
3
43
0
Order By: Relevance
“…A number of defined RBPs can be used to recognize and sort RNAs with specific binding motifs into exosomes (67)(68)(69). These specific motifs are shared by RNAs in EVs, which may facilitate their targeting to EVs.…”
Section: Exosomal Circrnas and Their Sorting Mechanismsmentioning
confidence: 99%
“…A number of defined RBPs can be used to recognize and sort RNAs with specific binding motifs into exosomes (67)(68)(69). These specific motifs are shared by RNAs in EVs, which may facilitate their targeting to EVs.…”
Section: Exosomal Circrnas and Their Sorting Mechanismsmentioning
confidence: 99%
“…However, there is a mounting consensus in the literature suggesting miRNAs are not the most abundant RNA species in EVs. Rather, fragments of other noncoding RNAs including ribosomal RNA (rRNA), transfer RNA (tRNA) YRNAs, 7S RNA, and Vault RNAs are generally more abundant in EVs than individual miRNAs and their levels in EVs are enriched compared to intracellularly (Chahar, Corsello, Kudlicki, Komaravelli, & Casola, ; Driedonks et al, ; Lässer et al, ; Nolte‐'t Hoen et al, ; Pérez‐Boza, Lion, & Struman, ; Tosar et al, ; Wei et al, ). Although fragmented noncoding RNAs have historically been considered degradation products, in many cases the fragments arise from specific processing events.…”
Section: Looking Beyond Mirnas—ribosomal Rna and Transfer Rna Fragmenmentioning
confidence: 99%
“…The content of exosomes is dictated by the parent cell type, as well as by the status and the environment of the cells at the time of production [3]. Even though exosomes may carry different cargo (coding and non-coding RNA [4], DNA [5], lipids [6] and proteins [7]), multiple studies have shown that the loading of specific RNAs (in disease) can promote phenotypic changes in the recipient cells [8].…”
Section: Introductionmentioning
confidence: 99%